A novel antimicrobial composite: ZnAl-hydrotalcite with p-hydroxybenzoic acid intercalation and its possible application as a food packaging material. (2nd December 2019) - Cheng, Hui-Min; Gao, Xue-Wei; Zhang, Kang; Wang, Xin-Rui; Zhou, Wei; Li, Shu-Jing; Cao, Xue-Li; Yan, Dong-Peng
Abstract : p -Hydroxybenzoic acid was intercalated into LDHs (Zn/Al ratio = 4 : 1). The former possesses anti-fungal activity and the latter shows the best antibacterial effect. Abstract : Microbial contamination poses a great threat to people's life and health. In this paper, p -hydroxybenzoic acid (PHBA) was intercalated into layered double hydroxides (LDHs, with Zn : Al molar ratio = 4 : 1); the former possesses the antifungal effect for Candida albicans, and the latter shows the best antibacterial effect for Staphylococcus aureus . The sample was characterized by XRD, FT-IR spectroscopy and TG-DTA. Its sustained-release property was studied by a release experiment. Finally, ZnAl-PHBA-LDH (Zn : Al = 4 : 1) was dispersed into the solution of gelatin to obtain a food packaging film; antimicrobial experiments showed that the gelatin film of ZnAl-PHBA-LDH (Zn : Al = 4 : 1) (ZPL4) could effectively inhibit the activity of Staphylococcus aureus and Candida albicans . The experimental results confirm the application of ZPL4 in the field of food antimicrobial packaging.